THE CORRELATION BETWEEN EMOTIONAL INTELLIGENCE AND LEARNING ACHIEVEMENTS OF STUDENTS IN THE ENGLISH EDUCATION DEPARTMENT - Sahril Sahril; Badruddin Kaddas; Jusmaniar N (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2025)
Abstract: This study aims to determine whether there is a relationship between students' Emotional Intelligence (EI) and learning Achievement of students in the English Education Department Universitas Islam Makassar. This research used correlational design. And the total sampling used as the sample of this study amounted to 40 students. The data in this study were obtained using a questionnaire and documentation, utilizing a 33-item Likert scale questionnaire to assess Emotional Intelligence (EI). The data on students’ emotional intelligence and English academic achievement were analyzed by using Pearson Product Moment correlation analysis through SPSS 30 to find out whether or not there was correlation between them. The final finding in this study shows that Pearson correlation analysis revealed no significant correlation between EI and GPA (r = .017, p > .05). This suggests that, within this specific population, cognitive factors may be more influential determinants of academic success than EI. Further research is recommended to explore other factors influencing academic achievement and to investigate potential differences in EI's impact across various student populations and educational contexts. Keywords: Emotional Intelligence, English, Learning Achievement